Incidence of Borrelia garinii and Borrelia afzelii in Ixodes ricinus ticks in an urban environment, Prague, Czech Republic, between 1995 and 1998 - Basta, J; Plch, J; Hulínská, D; Daniel, M (European journal of clinical microbiology & infectious diseases, 1999)
The presence of Borrelia burgdorferi sensu lato and its individual genospecies was determined using a single-step polymerase chain reaction in a total of 779 Ixodes ricinus ticks collected from an urban park in Prague, Czech Republic. The incidence of Borrelia burgdorferi sensu lato was 9.2% in 1995, 3.4% in 1996, 4.5% in 1997 and 2.8% in 1998. The Borrelia garinii to Borrelia afzelii ratio was 1.4:1 and it did not differ significantly throughout the study period. Borrelia burgdorferi sensu stricto was not detected. Borrelia garinii/Borrelia afzelii coinfection was found in 5.7% of positive ticks. The results indicate it is possible for the urban population to come in contact with the causative agent of Lyme disease in an urban park.
Keywords: Urban Health; Borrelia Infections; lymeská nemoc; Ixodes; Lyme Disease; klíště; Animals; Humans; Česká republika; Borrelia burgdorferi komplex; Borrelia; lidé; zdraví ve městech; zvířata; Czech Republic; Borrelia burgdorferi Group; infekce bakteriemi rodu Borrelia